The predictive value of handheld peak expiratory flow metre and IPAG questionnaire as a screening tool for COPD among high-risk patients - Oluwajimi O. Sodipo; Tunde O. Oluwafemi; Adejumo O. Adedeji; Kunle Ibrahim; S. Odunaye-Badmus; Esther O. Oluwatuyi; Ruth Odiana (Nigerian Frontline Medicine Journal)
Introduction: Chronic Obstructive pulmonary Disease (COPD) is increasing in Africa due to multiple risk factors like smoking and use of biomass fuels'. There are challenges in the diagnosis of COPD at primary care due to scarcity of spirometers.